Pengaruh Pemberian Snack Fig Bar Tepung Kacang Kedelai Dan Ubi Jalar Kuning Terhadap Tekanan Darah Penderita Hipertensi Di Puskesmas Kertapati Palembang - Ummi Zahra; Manuntun Rotua; Susyani Susyani; Nathasa Weisdania Sihite (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2022)
Background: Hypertension that occurs in productive age in Indonesia is a serious health problem, the prevalence is above 34.1%. Lack of intake of macro and micro nutrients is the main cause of the lack of healthy snacks, especially for people with hypertension. nutritional intervention with Fig Bar Snack Formula which can significantly reduce the incidence of hypertension. Snack Fig Bar is a type of bakery when broken solid textured. Soybeans and Yellow Sweet Potatoes contain potassium and fiber which play a role in lowering systolic and diastolic blood pressure. Purpose: This study aims to determine the effect of giving FIG BAR snacks made from soybean flour and yellow sweet potato flour on reducing blood pressure in hypertension. Method: The type of research used is a quasi-experimental with a Control Group Pretest-Posttest design. This research was conducted from January to April 2022 at the Kertapati Health Center in Palembang. The sample in this study was selected by Systematic Random Sampling with a total sample of 30 treatment respondents and 30 comparison respondents.Result: Data analysis using t-dependent that the average systolic and diastolic blood pressure before treatment in the treatment group were 155.40 mmHg and 95.33 mmHg, in the comparison group 151.10 mmHg and 96.37 mmHg Conclusion: The average systolic and diastolic blood pressure after treatment in the treatment group was 151.97 mmHg and 93.23 mmHg, in the comparison group it was 157.53 mmHg and 96.60 mmHg with a p-value of 0.000 which indicates that there is an effect of giving snacks. Fig Bar Made from Soybean Flour and Yellow Sweet Potato Flour for Hypertension Patients' Blood Pressure.